THE IMPACT OF PATIENTS’ GENDER, RACE, AND AGE ON HEALTH CARE PROFESSIONALS’ PAIN MANAGEMENT DECISIONS: AN ONLINE SURVEY USING VIRTUAL HUMAN TECHNOLOGY - Wandner, Laura D. (2013)
BACKGROUND: Previous literature indicates that biases exist in pain ratings. Healthcare professionals have been found to use patient demographic cues such as sex, race, and age when making decisions about pain treatment. However, there has been little research comparing healthcare professionals’ (i.e., physicians and nurses) pain decision policies based on patient demographic cues. METHODS: The current study used virtual human technology to examine the impact of patients’ sex, race, and age on healthcare professionals’ pain ratings. One hundred and ninety-three healthcare professionals (nurses and physicians) participated in this online study. RESULTS: Healthcare professionals assessed virtual human patients who were male and African American to be experiencing greater pain intensity and were more willing to administer opioid analgesics to them than to their demographic counterparts. Similarly, nurses were more willing to administer opioids make treatment decisions than physicians. There was also a significant virtual human-sex by healthcare professional interaction for pain assessment and treatment decisions. The sex difference (male > female) was greater for nurses than physicians. CONCLUSIONS: Results replicated findings of previous studies using virtual human patients to assess the effect of sex, race, and age in pain decision-making. In addition, healthcare professionals” pain ratings differed depending on healthcare profession. Nurses were more likely to rate pain higher and be more willing to administer opioid analgesics than were physicians. Healthcare professionals rated male and African American virtual human patients as having higher pain in most pain assessment and treatment domains compared to their demographic counterparts. Similarly the virtual human-sex difference ratings were more pronounced for nurses than physicians. Given the large number of patients seen throughout the healthcare professionals’ careers, these pain practice biases have important public health implications. This study suggests attention to the influence of patient demographic cues in pain management education is needed.